(3GdfbhT GdTGgOjI aj WQGHdS GdZQH EHGf GdYUQ GdYKeGfj GdChd h GdYUQ GdbQeGfdi (B958 - 1251(3g` (B/ 1551 - 1835(3e(B: s (3OQGSI BKGQjI afjI (B/ s - (3SgGe YHOGddg LGO YHOGddgs; (3UdGM CMeO GdHgfSi (B: s; (3eMeO MeRI ESeGYjd GdMOGO (B: s ((3GdbGgQI (B: s (3SgGe YHOGddg LGO YHOGddg (B: s, 2010)
(3Jcef GgejI GdHMK ai Cfg jJfGhd fbhT TGgOjI ef WQGHdS GdZQH ai GdaJQI (B958 - 1251(3g` (B/ 1551 - 1835(3e de JOQS ef bHd (B.(3GHQR GdHGMK GgejI ehVhY GdfbhT GdTGgOjI HdjHjG h JhVjM ecGfJgG Hjf GdHdGO GdCNQi HfbhT TGgOjI eeGKdI h eJRGefI eY gPjf GdYUQjf hJJHY GdCfSGH ef JSdSd GdCSeGA GdhGQOI Ydi eLehYI ThGgO GdOQGSI h OQGSI GdUjZ h GdeVGejf GdhGQOI ai GdfbhT GdTGgOjI ef BjGJ bQBfjI h COYjI ebJHSI ef GdbQBf h ZjQ Pdc ef CSeGA h CdbGHs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBKGQ (B- (3bSe GdBKGQ GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdCTYGQs; (3GdUjZs; (3GdfbhTs